The state of scientific research on the problems of investigating criminal offenses related to domestic violence (Law and Safety, 2022)
An attempt was made to trace the change in approaches to the understanding of the concepts of “domestic violence” and “offenses related to domestic violence” and, based on the meaningful correlation of these categories, to reveal the trends in the development of scientific opinion on countering these offenses, primarily of a criminal law nature. Emphasis is placed on highlighting the achievements of Ukrainian scientists in works devoted to the problems of pre-trial investigation of criminal offenses related to domestic violence. Based on the results of the analysis, the author's periodization of the development of scientific thought in the specified field has been proposed.As a result of the conducted research, some regularities of the development of the criminal procedural opinion based on the research of the problems of pre-trial investigation of criminal offenses related to domestic violence have been outlined. The first conclusion indicates the gradual development of such studies, which is connected with the change of the material and legal basis, that is, the criminal legislation, which at different times provided a different qualifying model of criminal offenses related to domestic violence. Thus, at the first stage (until 2017), domestic scientists mostly directed their attention to the study of criminal law and criminological problems of combating criminal offenses included in the concept of “crimes related to domestic violence”. There are only separate works of a criminal procedural or forensic nature, aimed at solving the problems of investigating a set of types of criminal offenses included in the concept of “crimes related to domestic violence”.The next stage (since 2017) is related to the criminalization of domestic violence (Article 126-1 “Domestic Violence” was added to the Special Part of the Criminal Code of Ukraine). It is natural that the specified event aroused interest among scientists and, in particular, shifted the emphasis of scientific research to the problems of investigating domestic violence within the scope of one crime.Currently, the beginning of the transition to the third stage of the development of scientific research on the problems of investigating criminal offenses related to domestic violence is observed. The latter is characterized by a shift in the emphasis of scientists to researching the problems of investigating other types of criminal offenses related to domestic violence, other than those provided for in Art. 126-1 “Domestic violence” of the Criminal Code of Ukraine, for example, a study of the problems of investigating murders committed with the use of domestic violence.
Keywords: domestic violence; pre-trial investigation; development of scientific thought.